Flight Control System for a Hydrofoil Boat: Controller development by performance analysis in the Unity simulation environment - Hörberg, Andreas; Lundgren, Felix (My University, 2023)
The hydrofoil technique has awakened a renewed interest among boat builders, and because of this there are opportunities for innovation. Hydrofoiling relies on adjustments of the angle of attack of the attached hydrofoil wings, thereby necessitating effective control to support stability and robustness. However, due to its recent resurgence, there is limited availability of existing controllers, motivating the foundation of this thesis. This project is structured around research questions, and an objective, which is to develop a controller that can effectively implement the hydrofoil technique. In this endeavor, a controller is successfully developed and tested within a simulation environment, primarily driven by the key findings which are obtained throughout the project’s progression. These key findings play a crucial role in achieving the functional controller and providing answers to the research questions.
Keywords: Angle of Attack; Flight Controller; Drag Force; Front Foil Compensation; Hydrofoil; Lift Force; Unity; Simulation